EVALUATING THE EFFECTIVENESS OF JUVENILE JUSTICE SYSTEMS: A COMPARATIVE ANALYSIS OF REHABILITATION VS. PUNITIVE APPROACHES IN INDIA - Joshi, Vidhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Over the years, the Indian Juvenile Justice system has gone through significant changes, specifically after the implementation of the Juvenile Justice (Care and Protection of Children) Act, 2015. The research conducted in this research paper (“Paper”) focuses on solving the problem statement and understanding the effectiveness of rehabilitation versus punitive approaches in addressing juvenile delinquency. Based on empirical data, legal framework, and institutional practices, this Paper explores how these approaches influence recidivism, reintegration, and long-term outcomes for juvenile offenders. The Paper concludes that while punitive measures may serve immediate deterrent purposes, rehabilitation offers more sustainable and humane outcomes, especially in a development context. As of today, this Paper utilizes contemporary data and scholars’ research to analyse India’s Juvenile Justice Systems, emphasizing the tension between rehabilitative and punitive approaches. It concludes with the policy recommendations to better align India’s Juvenile Justice Systems efforts with global child rights standards and constitutional values.